Heavy flavours in high-energy nuclear collisions: quenching, flow and correlations. (April 2015) - Beraudo, A; De Pace, A; Monteno, M; Nardi, M; Prino, F
Abstract: We present results for the quenching, elliptic flow and azimuthal correlations of heavy flavour particles in high-energy nucleus-nucleus collisions obtained through the POWLANG transport setup, developed in the past to study the propagation of heavy quarks in the Quark-Gluon Plasma and here extended to include a modeling of their hadronization in the presence of a medium. Hadronization is described as occurring via the fragmentation of strings with endpoints given by the heavy (anti-)quark and a thermal parton from the medium. The flow of the light quarks is shown to affect significantly the R AA and v 2 of the final D mesons, leading to a better agreement with the experimental data.